El poder y la gloria : élites y asientos militares en el astillero de la Habana durante el siglo XVIII (2013)
ABSTRACT: Throughout the 18th century, Havana’s shipyard served to reveal the conflict of interests between the local elite and Spain’s imperial needs in the Caribbean. Power, associated with wealth, and glory, which came from social position, were the driving forces of the collaboration between the powerful upper echelons of Havana and the political-military authorities sent from the Peninsula. Military bases were one of the means to achieve both ends, and gave rise to endless struggles over the vital military arsenal, a source of riches, power and constant intrigue. This work illustrates the panorama of this cooperation, equally a necessity and an obligation.